NEW EDUCATION TECHNOLOGY IN MATHEMATICS - MIŠÚTOVÁ, Mária (Trends in education, 2009)
The results of the research project are described in this article. Research project deals with the student's attitudes towards mathematics and creativity.
Keywords: mathematics; creativity; attitudes; open source software.